Design of a Portable Quick‑Release Drive System for Conventional Manual Wheelchairs to Enhance Comfort and Accessibility - Siregar, Rolan; Owen, Michael; Purba, Samuel Parsadaanta (Jurnal Rekayasa Mesin, 2026)
Conventional manual wheelchairs are widely used for indoor mobility; however, their operation is limited by the user’s ability to generate propulsion force, which affects travel range and the level of independence. This study presents the design and development of a portable drive system equipped with a quick-release mechanism, enabling fast installation and removal without permanent modification to the wheelchair. The proposed system employs a 120 W DC motor and a 24 V, 4.5 Ah battery. The research methods include mechanical and electrical power requirement calculations, CAD-based design, finite element analysis (FEA) for structural strength verification, and prototype fabrication. Simulation results indicate that the structure can support an 80 kg load with a safety factor of 1.23. The prototype achieves a maximum speed of approximately 15 km/h, with an operating time of about 1 hour at maximum load. The proposed quick-release portable drive system is expected to enhance user mobility and independence, thereby improving comfort and accessibility in everyday use.